ABBOT PREND DOCI, AN EXEMPLARY FIGURE IN THE ALBANIAN NATIONALISM - Ljarja, Nertila Haxhia (European Scientific Journal, ESJ, 2015)
Prend Doci was born on 7th February 1846 in the Bulger village of Lezha. He was one of the first students in the Papnuer Seminar in Shkoder which began on the 2nd of August 1859 and after a short while, in 1861 he was sent to Rome at the Urban Propoganda College. Upon completion of his theological studies in 1871 he returned to Albania where he became a local priest in Korthpule (one of the poorest church in Mirdita). He then went on to become Chaplain for Archbishop Gasper Krasniqi and Abbot for She Lleshari in Orosh. In 1876-1877 he became a priest in Kalivare where he organized and influenced events during these years.